TOURISM AND CARBON FOOT PRINTS IN UNITED ARAB EMIRATES – CHALLENGES AND SOLUTIONS - VIJ, Mohit; VIJ, Anu (Journal of Environmental Management and Tourism, 2016)
The article brings into picture the tourism progression and its environmental consequences in a recently emerged international tourist destination, United Arab Emirates (UAE). The country attracted around 8 million tourists in the year 2008 and at the same time made to the news-lines for generating highest carbon footprints per capita in the world! The article intends to generate a comprehensive analysis on background of United Arab Emirates (UAE), its resources, infrastructure and relevance of developing tourism which is strongly emphasized on energy intensive “man made tourism resources”. The article is divided into three sections to assess the challenges and solutions related to tourism and environment in the country. In the first section, an analysis is drawn on the background of United Arab Emirates (UAE), its resources, infrastructure and progression made in the tourism sector. At the same time a discussion is made on the prevailing environment problems in the country and its status in terms of environment performance with regard to other countries. The second section of the paper throws light over the attempts made by the UAE government and major tourism stakeholders to deal with the current situation. A summary of these attempts and environmental laws is also taken into consideration under this section. In the last section, three carbon mitigation methodologies have been identified which best suit the prevailing condition and requirements in the UAE. A special investigation is also carried out to evaluate the business potential of these methodologies attracting the investors’ interest.
Keywords: UAE; GHG emissions; climate change; carbon footprints; tourism